Nuclear receptors EcR, Usp, E75, DHR3, and ERR regulate transcription of ecdysone cascade genes. - Mazina, M.Y.; Kocheryzhkina, E.V.; Nikolenko, J.V.; Krasnov, A.N.; Georgieva, S.G.; Vorobyeva, N.E. (Doklady. Biochemistry and Biophysics, 2017)
We found that an increase in the expression level of E75, DHR3, and ERR increases the degree of activation of dhr3 and hr4 genes in Drosophila S2 cells. We also detected a repressing effect of these nuclear receptors on the basal transcription level of these genes. This is the first study to show the ability of nuclear receptors E75, DHR3, and ERR to function as activators or repressors depending on external conditions. We also confirmed the existence of the interaction of all studied nuclear receptors with the promoters of dhr3 and hr4 genes of the ecdysone cascade in vivo.